Conflict resolution, public goods and patent thickets - Dietmar Harhoff; Georg von Graevenitz; Stefan Wagner (European School of Management and Technology (ESMT), 2013)
Post-grant validity challenges at patent offices rely on the private initiative of third parties to correct mistakes made by patent offices. We hypothesize that incentives to bring post-grant validity challenges are reduced when many firms benefit from revocation of a patent and when firms are caught up in patent thickets. Using data on opposition against patents at the European Patent Office we show that opposition decreases in fields in which many others profit from patent revocations. Moreover, in fields with a large number of mutually blocking patents the incidence of opposition is sharply reduced, particularly among large firms and firms that are caught up directly in patent thickets. These findings indicate that post-grant patent review may not constitute an effective correction device for erroneous patent grants in technologies affected by either patent thickets or highly dispersed patent ownership.
urn:nbn:de:101:1-2013071912559
Keywords: K11; K41; O34; 650; intellectual property; opposition; patent litigation; patent thickets; patents; post-grant review; Patent; Zivilprozess; Konfliktregelung; Ökonomischer Anreiz; Öffentliche Güter; EU-Staaten